2001
DOI: 10.1002/dmrr.219
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acipimox on the lipolysis rate in subcutaneous adipose tissue of obese subjects

Abstract: In the present study basal glycerol outflow from adipose tissue was inhibited by acipimox. The anti-lipolytic action of the agent may diminish elevated plasma concentrations of free fatty acids in subjects with severe obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…However, effects on oxidation rates may be limited, as ACI preferentially improves nonoxidative glucose disposal. Moreover, ACI stimulates skin blood flow (7); however, we do not suspect this to have a major impact on the tracer kinetics, as ACI has no effect on adipose tissue (9) or forearm blood flow (12,29). Second, our results cannot be extended to women or other patient groups.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, effects on oxidation rates may be limited, as ACI preferentially improves nonoxidative glucose disposal. Moreover, ACI stimulates skin blood flow (7); however, we do not suspect this to have a major impact on the tracer kinetics, as ACI has no effect on adipose tissue (9) or forearm blood flow (12,29). Second, our results cannot be extended to women or other patient groups.…”
Section: Discussionmentioning
confidence: 84%
“…Systemic palmitate flux and oxidation were measured using an isotope dilution technique, with a 1-h constant infusion of [9, (16,47). Data were insufficient in one participant.…”
Section: Methodsmentioning
confidence: 99%
“…There is evidence that acipimox directly affects lipolysis in sc adipose tissue. Using microdialysis techniques, Flechtner-Mors et al (39) showed decreased glycerol outflow and therefore decreased lipolysis from sc fat depots among obese individuals after acipimox treatment. These data suggest a potential specific benefit of acipimox for HIV-infected patients in whom increased lipolytic rates in sc fat stores may contribute to increased FFA levels and to lipodystrophy.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was designed to test this hypothesis using acipimox, a nicotinic acid derivative that suppresses both peripheral tissue lipolysis (7,23) and hepatic triglyceride release (20). To clarify more fully the relationship between fatty acid supply and EGP, nondiabetic subjects with a wide range of body weights were studied.…”
mentioning
confidence: 99%